PENGARUH PELATIHAN, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DISDUKCAPIL KABUPATEN MANOKWARI - Nurjana Nurjana; MAKARIUS BAJARI; Selmi Dedi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2022)
ABSTRACTThe purpose of this study was to analyze the effect of training, competence and work discipline partially on employee performance at the Department of Population and Civil Registration of Manokwari Regency.This type of research uses a quantitative approach with the type of associative problem. The samplingtechnique used a saturated sample. The number of samples used were 31 employees at the Department of Population and Civil Registration of Manokwari Regency. The data analysis technique used multiple linear regression.